Bog child - Dowd, Siobhan (Oxford : David Fickling Books, 2010)
In 1981, the height of Ireland's "Troubles," eighteen-year-old Fergus is distracted from his upcoming A-level exams by his imprisoned brother's hunger strike, the stress of being a courier for Sinn Fein, and dreams of a murdered girl whose body he discovered in a bog.
Young Adult.
Young Adult
Keywords: Bog bodies -- Juvenile fiction; Families -- Ireland -- Juvenile fiction; Political prisoners -- Juvenile fiction; Political violence -- Juvenile fiction; Terrorism -- Juvenile fiction; Bog bodies -- Fiction; Family life -- Fiction; Political prisoners -- Fiction; Political violence -- Fiction; Terrorism -- Fiction; Bog bodies -- Fiction; Family life -- Ireland -- Fiction; Political prisoners -- Fiction; Terrorism -- Fiction; Ireland -- History -- 20th century -- Juvenile fiction; Ireland -- History -- Fiction; Ireland -- History -- Fiction